THE EFFECT OF LEADERSHIP AND COMPENSATION STYLE ON JOB SATISFACTION WITH WORK MOTIVATION AS A MEDIATION VARIABLE AT PT. JR BRANCH DKI JAKARTA - Faqih Restuanto; Tine Yuliantini (International Journal of Social Science, 2023)
PT. JR DKI Jakarta Branch as a state company engaged in social insurance, as well as other companies that need Human Resources who are competent and able to compete and help the company achieve its vision and mission so that the company continues to grow and continue in the future. The purpose of this research is to analyze the effect of leadership style and compensation on job satisfaction with work motivation as a mediating variable at PT. JR DKI Jakarta Branch. This study uses quantitative methods to determine the relationship and influence between variables, with 75 respondents. The sample selection uses the saturated sample method and data collection uses a questionnaire. Data is processed using Structural Equation Modeling (SEM) using SMART-PLS. The results of this study indicate that leadership style and compensation have a significant effect on work motivation. Leadership style has a significant effect on job satisfaction, while compensation has no significant effect on job satisfaction. Motivation has a significant effect on job satisfaction. Leadership Style and Compensation have a significant effect on Job Satisfaction which is mediated by work motivation